Altered miRNA and gene expression in acute myeloid leukemia with complex karyotype identify networks of prognostic relevance - Rücker, Frank Gert; Russ, A. C.; Cocciardi, S.; Kett, H.; Schlenk, R. F.; Botzenhardt, U.; Langer, C.; Krauter, J.; Fröhling, S.; Schlegelberger, B.; Ganser, A.; Lichter, Peter; et al. (Leukemia, 2013)
Recently, the p53-miR-34a network has been identified to have an important role in tumorigenesis. As in acute myeloid leukemia with complex karyotype (CK-AML) TP53 alterations are the most common known molecular lesion, we further analyzed the p53-miR-34a axis in a large cohort of CK-AML with known TP53 status (TP53altered, n=57; TP53unaltered, n=31; altered indicates loss and/or mutation of TP53). Profiling microRNA (miRNA) expression delineated TP53 alteration-associated miRNA profiles, and identified miR-34a and miR-100 as the most significantly down- and upregulated miRNA, respectively. Moreover, we found a distinct miR-34a expression-linked gene expression profile enriched for genes belonging to p53-associated pathways, and implicated in cell cycle progression or apoptosis. Clinically, low miR-34a expression and TP53 alterations predicted for chemotherapy resistance and inferior outcome. Notably, in TP53unaltered CK-AML, high miR-34a expression predicted for inferior overall survival (OS), whereas in TP53biallelic altered CK-AML, high miR-34a expression pointed to better OS. Thus, detailed molecular profiling links impaired p53 to decreased miR-34a expression, but also identifies p53-independent miR-34a induction mechanisms as shown in TP53biallelic altered cell lines treated with 15-deoxy-Δ12,14-prostaglandin. An improved understanding of this mechanism might provide novel therapeutic options to restore miR-34a function and thereby induce cell cycle arrest and apoptosis in TP53altered CK-AML.
Advance online publication, 10 August 2012
Gesehen am 24.01.2022